Analisis Kelayakan Ekonomi Mesin Pencacah Rumput Gajah Tipe Reel - Wahyu Kristian Sugandi; Asep Wahyu (Fakultas Pertanian Universitas Padjadjaran, 2018)
ABSTRACTEconomic analysis reel type cutting machine for elephant grassThe need grass for fodder in the region Lembang has been increasing, but it does not followed by its quality. Therefore, cutting machine which is able to cut the fodder no more than 5 cm size is needed. The Laboratory of Agricultural Machinery and Machinery Department of Agricultural Engineering and Biosystem FTIP Unpad had been developed an elephant grass enchant machine in accordance with the requirements of making the silage, but no economic feasibility analysis has been done for the machine. Therefore it was necessary to study the economic feasibility analysis of elephant grass cutting machine. The method used in this study was the economic analysis method which includes the cost ofproduction and the breakeven point, and business feasibility including net present value (NPV), benefit cost ratio analysis (BCR), internal rate of return (IRR) and payback period analysis (PBP). The results showed that the cost of production of elephant grass enemies was Rp 2,178 / kg with production breakeven 18.769 kg, BC ratio of 1.15, NPV1 of Rp 70,770, - NPV2 of Rp 61.333, - IRR of 27% and payback period during 2 months. So it can be concluded that the use of elephant-type elephant chopper machine was feasible to use.Keywords: Elephant grass, economic analysis, cutting machineABSTRAKKebutuhan rumput gajah untuk pakan ternak (silase) di daerah Lembang terus meningkat. Syarat pembuatan silase tersebut bahwa panjang potongan rumput gajah sebaiknya < 5 cm. Untuk itu diperlukan sebuah mesin pencacah rumput gajah sesuai syarat pembuatan silase. Laboratorium Alat dan Mesin Pertanian Departemen Teknik Pertanian dan Biosistem FTIP Unpad telah mengembangkan sebuah mesin pencacah rumput gajah sesuai syarat pembuatan silase tersebut, tetapi belum dilakukan analisis kelayakan ekonomi untuk mesin tersebut. Oleh karena it diperlukan suatu penelitian berkenaan dengan analisis kelayakan ekonomi mesin pencacah rumput gajah. Metode yang digunakan pada penelitian ini adalah metode analisis ekonomi yang meliputi biaya pokok produksi dan titik impas, serta kelayakan usaha yang meliputi net present value (NPV), benefit cost ratio analysis (BCR), internal rate of return (IRR) dan payback period analysis (PBP). Hasil penelitian menunjukkan bahwa biaya pokok produksi mesin pencacah rumput gajah adalah Rp 2.178/kg dengan titik impas produksi 18.769 kg, BC rasio sebesar 1,15, NPV 1 sebesar Rp 70.770,- NPV 2 = Rp 61.333,-IRR sebesar 27% dan payback period selama 2 bulan. Maka dapat disimpulkan bahwapengunaan mesin pencacah rumput gajah tipe reel layak digunakan.Kata Kunci : Rumput Gajah, Analisis Ekonomi, Mesin Pencacah